Two approaches of adaptive control of the object with elastic connections: Using the reference model and the use of fuzzy logic algorithms - Lukichev, Dmitry V.; Demidova, Galina L. (2017 IEEE Conference of Russian Young Researchers in Electrical and Electronic Engineering (EIConRus), 2017)
Modern electromechanical systems due to the respective electric drives control algorithms, have to ensure maximum achievable requirements for precision and control dynamics of the spatial coordinates of the bodies that make up their structure. The features of these systems are changing the dynamic parameters, which include, changing the moment of inertia of bodies relative to the axis of rotation, as well as the impact of the external environment, for example in the form of wind moment with a random character. Availability of nonlinear moments of dry friction in the systems' construction leads to self-oscillation speed and position (the so-called "stepping" mode), unacceptable for precision devices. The article presents a comparative analysis of two algorithms for control of object with elastic connections: use the reference model in the forward loop and use of adaptive fuzzy PID controller. It is shown that both of these methods allow to remove the self-oscillations. However, the system with adaptive fuzzy PID controller has better dynamic performance and is robust in the case when the parameters of the controlled object change.